Quantitative Analysis of Magnetohdrodynamic Sustained Convective Flow via Vertical Plate - Kirubaharan, D R; Subhashini, A D; Babu, Narendra V.N; Murali, Gundagani (International Journal of Applied Sciences and Smart Technologies, 2024)
In this paper, the effects of heat and mass transfer on MHD flow in an incompressible, heated fluid that has been accelerated to a steady free stream are investigated. It examines mass movement in a magnetic field as well as heat absorption qualities. In the model, non-linear governing equations and the Laplace transform method are applied. The relationship between temperature, concentration, and velocity and flow parameters is illustrated by studies utilizing parametric data.Keywords: Magnetohdrodynamics, Laplace Transform method, Free Convection, vertical Plate